2017
DOI: 10.3389/fpls.2017.00871
|View full text |Cite
|
Sign up to set email alerts
|

Chloroplast- or Mitochondria-Targeted DEAD-Box RNA Helicases Play Essential Roles in Organellar RNA Metabolism and Abiotic Stress Responses

Abstract: The yields and productivity of crops are greatly diminished by various abiotic stresses, including drought, cold, heat, and high salinity. Chloroplasts and mitochondria are cellular organelles that can sense diverse environmental stimuli and alter gene expression to cope with adverse environmental stresses. Organellar gene expression is mainly regulated at posttranscriptional levels, including RNA processing, intron splicing, RNA editing, RNA turnover, and translational control, during which a variety of nucle… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
39
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
5
5

Relationship

1
9

Authors

Journals

citations
Cited by 65 publications
(40 citation statements)
references
References 77 publications
1
39
0
Order By: Relevance
“…4B). Several previous studies have suggested that RNA helicases play a pivotal role in plant stress responses (Liu et al, 2002;Owttrim, 2006;Vashisht and Tuteja, 2006;Kant et al, 2007;Nawaz and Kang, 2017). Because these enzymes mediate localized unwinding of RNAs, they might well become critical at low temperatures, which are expected to stabilize RNA secondary structure (Herschlag, 1995;Jones and Inouye, 1996;Lorsch, 2002).…”
Section: Rh50 Promotes Biogenesis Of the Plastid Ribosome Bymentioning
confidence: 99%
“…4B). Several previous studies have suggested that RNA helicases play a pivotal role in plant stress responses (Liu et al, 2002;Owttrim, 2006;Vashisht and Tuteja, 2006;Kant et al, 2007;Nawaz and Kang, 2017). Because these enzymes mediate localized unwinding of RNAs, they might well become critical at low temperatures, which are expected to stabilize RNA secondary structure (Herschlag, 1995;Jones and Inouye, 1996;Lorsch, 2002).…”
Section: Rh50 Promotes Biogenesis Of the Plastid Ribosome Bymentioning
confidence: 99%
“…Chloroplast gene expression is regulated mainly at post‐transcriptional levels, including pre‐mRNA splicing, RNA editing and RNA degradation, processes for which a variety of RNA‐binding proteins (RBPs) are vital (Jacobs and Kück, ; Germain et al ., ). In particular, many nucleus‐encoded RBPs are targeted to the chloroplast and play essential roles in the splicing of chloroplast introns (Jenkins et al ., ; Barkan et al ., ; Falcon de Longevialle et al ., ; Bryant et al ., ; Nawaz and Kang, ).…”
Section: Introductionmentioning
confidence: 98%
“…However, the ability of these introns to perform self-splicing in vivo has been lost, and thus additional nuclear-and/or plastid-encoded splicing cofactors are required to accomplish intron splicing (Bonen and Vogel 2001;de Longevialle et al 2010). Such cofactors include the plastid maturase matK, chloroplast RNA splicing and ribosome maturation proteins, pentatricopeptide repeat (PPR) proteins, RNA helicases, mitochondrial transcription termination factors, a RNase III domain-containing protein, WHAT IS THIS FACTOR 1 (WTF1) and a WHY and UMP kinase (de Longevialle et al 2010;Quesada 2016;Nawaz and Kang 2017;Schmid et al 2019). Of these cofactors, PPR proteins not only play vital roles in intron splicing, but also in RNA editing, RNA processing, RNA stability and RNA translation (Barkan and Small 2014).…”
Section: Introductionmentioning
confidence: 99%